CE-24 Comparison of systemic lupus erythematosus in 3 different asian ethnic groups: results from the 1000 canadian faces of lupus cohort. (31st August 2016) - Nguyen, Mai; Fortin, Paul R; Silverman, Earl; Pope, Janet; Chedeville, Gaelle; Huber, Adam; Bernatsky, Sasha; Clarke, Ann; Pineau, Christian; Hudson, Marie; Arbillaga, Hector; Tucker, Lori; et al.
Abstract : Background: Systemic lupus erythematosus (SLE) is more prevalent and severe in non-Caucasians including Asians. However, Asian ethnicity includes broad geographic, cultural, and genetic diversity. There is limited data examining SLE among North American Asian ethnicities. We describe SLE in 3 Asian subgroups from a large SLE cohort. Materials and methods: The 1000 Faces of Lupus is a multicenter Canadian cohort of over 2000 patients. Sociodemographics, ACR classification criteria (ACRc), autoantibodies, disease activity scores (SLEDAI), Systemic Lupus International Collaborating Clinics damage index (SDI) scores, and treatments are collected using standardised tools. Ethnicity was self-reported. Asian subgroups were divided by origin country into East Asian (EA), Southeast Asian (SEA), South Asian (SA) and Central Asian (CA). Baseline data for Asians and Caucasians were abstracted and cross-sectional univariate analyses including t-tests, one-way ANOVA, and chi-square tests were performed. Results: There were 334 Asians (EA = 176, SEA = 78, SA = 78, CA = 2), and 1275 Caucasians. CA were excluded. Mean Asian onset age was younger (EA = 23 ± 13 years; SEA = 21±10 years; SA = 20 ± 11 years, Caucasian 33 ± 15 years, p < 0.001), but this was due to very frequent childhood onset in Asians (EA = 49%; SEA = 51%; SA = 61%) compared to Caucasians (17%, p < 0.001) (Figure 1 ). Over 40% of Asians were immigrants, and a higher proportion were males (EA = 15%; SEA = 16%; SA = 19%) compared to Caucasians (10%, p = 0.008). More Asians (90%) completed high school compared to Caucasians (83%, p = 0.007). Income was similar between all Asian subgroups and Caucasians. ACRc and SLEDAI scores were not different, but nephritis was more frequent in all Asians: (EA = 57%; SEA = 63%; SA = 51%) compared to Caucasians (33%, p < 0.001). Asians were more frequently (ever) seropositive: (dsDNA+: EA = 62%; SEA = 63%; SA = 78%; Caucasians 52%, p < 0.001). (antiSm+: EA = 31%; SEA = 50%; SA = 30%; p = 0.01, Caucasian 19%, p < 0.001). (antiRNP+: EA = 20%; SEA = 32%; SA = 22%; p = 0.03, Caucasians 16%, p < 0.001). Treatment with prednisone (EA = 55%; SEA = 67%; SA = 65%), cyclophosphamide (EA = 13%; SEA = 21%; SA = 20%), and mycophenolate (EA = 15%; SEA = 19%; SA = 9%) was more frequent in Asians compared to Caucasians (40%, 10%, 8%, respectively, p < 0.001 for all) likely reflecting renal disease. Mean disease duration in Asians was 8 years but most had no damage (SDI = 0, EA = 66%; SEA = 64%; SA = 79%) compared to Caucasians (47%, p < 0.001). Conclusions: In this analysis comparing Asian ethnic subgroups, we found only subtle differences between EA, SEA, and SA with SLE; as expected disease appeared more severe than in Caucasians. However, a strikingly high proportion of all Asians had onset in childhood. Along with the high proportion who were new Canadians, this suggests the potential for a growing burden of SLE in this population. Future studies of outcomes and optimal treatments are indicated. Acknowledgements: Presented on behalf of Canadian Network for Improved Outcomes for Systemic Lupus Erythematous (CaNIOS) 1000 Faces Investigators.